The Effects of Domestic Violence on Violent Prison Misconduct, Health Status, and Need for Post-Release Assistance Among Female Drug Offenders in Taiwan - Lai, Yung-Lien (International journal of offender therapy and comparative criminology, 2018)
Although much research has documented the fact that a high percentage of female inmates serving sentences for drug offenses have experienced domestic violence prior to incarceration, little research has been done to explore the potential long-term impact of domestic violence on prison misconduct, health status, and the need for post-release assistance. Based on survey data for 633 female drug offenders collected from Taiwanese correctional facilities in 2014, about one third (32%) of the offenders reported experienced domestic violence at least once prior to their incarceration. In all, 27% of them experienced being violently abused by a spouse/coinhabitant. Multivariate regression analyses indicate that a prior history of domestic violence victimization contributes significantly to inmates' violent misconduct even after controlling for a set of potential intervening variables. In addition, female drug offenders who were the victims of domestic violence reported higher levels of health problems in the prison setting, and perceived need for greater after-release assistance.